Spicy Bilis / Faridah Hanum Hj Nosbah, Nazirah Mohd Noh and Muhammad Syafig Ahmad Bukhari - Hj Nosbah, Faridah Hanum; Mohd Noh, Nazirah; Ahmad Bukhari, Muhammad Syafiq (2010)
The name of our company is Spicy Bilis. We choose this name because it is related with our product that involve anchovies and chilly. The name of our product is also Spicy Bilis. So it’s easier for us to put the brand name. The strength of our product comes from the taste of it and of course the quality as well. Bandar Perda has been chosen that we pick because of the strategic location situated there. We choose these locations because it is situated near the residential area, police station, hospital and as well as educational institute. Therefore, there are a lot of target market and can gain healthy profit. In addition, Bandar Perda also is one of the cities that are growing rapidly day by day. Hence, with good location, we hope that our business will run smoothly, last long and expand throughout the year. Besides that, our company chooses this product because it has a big potential and demand due to drastic economic growth. Furthermore, food industry always expands as population increase. So, we have no doubt to involve in this industry and will never look back. In our business the most important aspect that we considered are the quantities, qualities and service that we offer to the customers. We want to provide the best service so that we can maintain good relationship with the customer. Our company consists of General Manager/ Administrator Offices, Operational officer, marketing and financial officer. Besides that, we also hire a labor to do the cooking, cleaning and delivery man to help maintain and manage our shop more efficient and effectively. By doing so, with the hard work and bless from Allah. We hope our business can run smoothly. Insyaalah.